[44th Don Carlos Palanca awards for literature] - Medina, Buenaventura S., Jr. (Animo Repository, 1994)
Three La Salle faculty members were among the 48 winners in the 44th Don Carlos Palanca Awards for Literature. They were Buenaventura S. Medina, Jr. (first and second prizes in the Filipino essay division), Simplicio Bisa (second in the Filipino short story category), and Marjorie Evasco (second place in the English essay division).